Improving the Back Surface Field on an Amorphous Silicon Carbide Thin‐Film Photocathode for Solar Water Splitting. Issue 11 (9th May 2018) - Perez‐Rodriguez, Paula; Cardenas‐Morcoso, Drialys; Digdaya, Ibadillah A.; Raventos, Andrea Mangel; Procel, Paul; Isabella, Olindo; Gimenez, Sixto; Zeman, Miro; Smith, Wilson A.; Smets, Arno H. M.
Abstract: Amorphous silicon carbide (a‐SiC:H) is a promising material for photoelectrochemical water splitting owing to its relatively small band‐gap energy and high chemical and optoelectrical stability. This work studies the interplay between charge‐carrier separation and collection, and their injection into the electrolyte, when modifying the semiconductor/electrolyte interface. By introducing an n‐doped nanocrystaline silicon oxide layer into a p‐doped/intrinsic a‐SiC:H photocathode, the photovoltage and photocurrent of the device can be significantly improved, reaching values higher than 0.8 V. This results from enhancing the internal electric field of the photocathode, reducing the Shockley–Read–Hall recombination at the crucial interfaces because of better charge‐carrier separation. In addition, the charge‐carrier injection into the electrolyte is enhanced by introducing a TiO2 protective layer owing to better band alignment at the interface. Finally, the photocurrent was further enhanced by tuning the absorber layer thickness, arriving at a thickness of 150 nm, after which the current saturates to 10 mA cm −2 at 0 V vs. the reversible hydrogen electrode in a 0.2 m aqueous potassium hydrogen phthalate (KPH) electrolyte at pH 4. Abstract : Smart layers : The photovoltaic and catalytic effect of a monolithic device for water splitting are decoupled for the first time. The interplay between charge‐carrier separation and collection and their injection into the electrolyte is thoroughly investigated by modifying the semiconductor/electrolyte interface in amorphous silicon carbide‐based photocathodes.